What every Adventist should know about 1888 - Wallenkampf, Arnold Valentin (Review and Herald Publ. Assn., 1988)
Foreword. 1. From Jesus to the Arid Hills of Gilboa. 2. Portents of the Minneapolis General Conference Session. 3. The 1888 Message. 4. Ellen White's Strong Endorsement. 5. What Happened at the 1888 General Conference Session?. 6. The Holy Spirit Shamefully Treated. 7. Why This Betrayal and Crucifixion of Jesus?. 8. Corporate Sin and Guilt. 9. The Aftermath of the Minneapolis General Conference Session. 10. The 1888 Message Falters. 11. A G Daniells Appraises the Fate of the 1888 Message. 12. Our Present Responsibility. 13. Conformity Versus Conversion. 14. The Challenge of 1888 to Us